A Subtype of Inhibitory Interneuron with Intrinsic Persistent Activity in Human and Monkey Neocortex - Bo Wang; Luping Yin; Xiaolong Zou; Min Ye; Yaping Liu; Ting He; Suixin Deng; Yanbo Jiang; Rui Zheng; Yun Wang; Mingpo Yang; Haidong Lu; et al. (Cell Reports, 2015)
A critical step in understanding the neural basis of human cognitive functions is to identify neuronal types in the neocortex. In this study, we performed whole-cell recording from human cortical slices and found a distinct subpopulation of neurons with intrinsic persistent activity that could be triggered by single action potentials (APs) but terminated by bursts of APs. This persistent activity was associated with a depolarizing plateau potential induced by the activation of a persistent Na+ current. Single-cell RT-PCR revealed that these neurons were inhibitory interneurons. This type of neuron was found in different cortical regions, including temporal, frontal, occipital, and parietal cortices in human and also in frontal and temporal lobes of nonhuman primate but not in rat cortical tissues, suggesting that it could be unique to primates. The characteristic persistent activity in these inhibitory interneurons may contribute to the regulation of pyramidal cell activity and participate in cortical processing.